DISCLOSURES OF THE CIRCULAR ECONOMY IN THE 2022 ASRRAT PLATINUM RATING COMPANY'S SUSTAINABILITY REPORT - Suangga, Asri; Riyang Mardini; Rudy Hartanto (UPT Publikasi Ilmiah UNISBA, 2024)
This study explores how a Circular Economy (CE) disclosure appears in a company's Sustainability Report. In particular, the existence of CE is analyzed using the 5R approach, namely: reduce, reuse, recycle, recover, and repair. The research uses qualitative and quantitative content analysis methods, with the 2021 Sustainability Report of 10 companies achieving the 2022 Asia Sustainability Reporting Rating Platinum rankings. The ten companies in question are four engaged in the banking sector, three chemical manufacturers, two energy, and one pharmacy. The research results show that the commitment to a circular economy has given rise to many innovations in reducing generation and reusing waste in companies operating in the energy and chemical industries, two business sectors that use non-renewable natural resources as the main raw material. In the pharmaceutical industry, encourage the use of incinerators as a means of burning B3 waste so that it is safe for the environment. Meanwhile, in the banking sector, commitment to a circular economy can be seen in efforts to reduce paper use, which is in line with the trend of digitalization of banking services, which tends to be paperless. The keywords reduce, reuse, and recycle (3R) are the most common in corporate sustainability reports. While the keywords recovery and repair only appear in 2 reports. Keywords : Circular Economy, Disclosure, Sustainability Reporting.